Complement in human diseases: lessons from complement deficiencies - Botto, Marina; Kirschfink, Michael; Macor, Paolo; Pickering, Matthew C.; Würzner, Reinhard; Tedesco, Francesco (Molecular immunology, 2009)
Complement deficient cases reported in the second half of the last century have been of great help in defining the role of complement in host defence. Surveys of the deficient individuals have been instrumental in the recognition of the clinical consequences of the deficiencies. This review focuses on the analysis of the diseases associated with the deficiencies of the various components and regulators of the complement system and their therapeutic implications. The diagnostic approach leading to the identification of the deficiency is discussed here as a multistep process that starts with the screening assays and proceeds in specialized laboratories with the characterization of the defect at the molecular level. The organization of a registry of complement deficiencies is presented as a means to collect the cases identified in and outside Europe with the aim to promote joint projects on treatment and prevention of diseases associated with defective complement function.
Gesehen am 16.06.2021